2023
DOI: 10.11646/phytotaxa.598.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Lyophyllum deqinense (Lyophyllaceae, Agaricales), a new species from southwestern China

Abstract: Lyophyllum deqinense sp. nov. is described and illustrated from Yunnan Province, China, based on morphological features and molecular (ITS and LSU) data. The species can be distinguished by a greyish brown to light brown pileus and obtuse central umbo of the pileus, inrolled margin, globose to subglobose basidiospores (5.7–7.2 × 5.5–6.8 µm), clavate basidia (24–34 × 7–10 µm), cespitose and gregarious habit in soil. L. pallidofumosum is similar to the new species in pileus and stipe color, and shape and size of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
4
4
0
Order By: Relevance
“…As a L.decastes complex, Clade a has 12 species most similar to Lyophyllum decastes, namely Lyophyllum (11,13,21,22,23,28,46,47,52,60,88). This result is broadly consistent with and surpasses those based on the phylogenetic analyses and morphology studies, which found 5 and 8 species, respectively (Moncalvo et al, 1993;Ma et al, 2022Ma et al, , 2023, also proving the reliability of our results.…”
Section: Figuresupporting
confidence: 92%
“…As a L.decastes complex, Clade a has 12 species most similar to Lyophyllum decastes, namely Lyophyllum (11,13,21,22,23,28,46,47,52,60,88). This result is broadly consistent with and surpasses those based on the phylogenetic analyses and morphology studies, which found 5 and 8 species, respectively (Moncalvo et al, 1993;Ma et al, 2022Ma et al, , 2023, also proving the reliability of our results.…”
Section: Figuresupporting
confidence: 92%
“…Notes: Lyophyllum yiqunyang is quite similar to L. deqinense in having an olive-greyish to greyish-orange pileus and subglobose to globose basidiospores, the L. deqinense basidia are shorter (24.1-33.8 × 7.3-9.9 µm). The pileipellis of L. deqinense is a cutis composed of parallel elements [18].…”
Section: Taxonomymentioning
confidence: 99%
“…Kühner (Yunnan, Tibet); L. transforme (Lapl.) Singer (Yunnan, Tibet, Qinghai, Liaoning, Heilongjiang); and L. shimeji (Yunnan) [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Larsson and Sundberg [10] provided ITS and LSU data, which provided more evidence for identifying species. Later, several Lyophyllum species were published based on ITS and LSU data [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%